2011
DOI: 10.4269/ajtmh.2011.10-0312
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of PAIR for Cystic Echinococcosis: Experience on a Large Series of Patients from Bulgaria

Abstract: We report our experience with puncture, aspiration, injection, and reaspiration (PAIR) for the treatment of cystic echinococcosis in Bulgaria. PAIR was performed in 230 patients with 348 echinococcal cysts. At 12-month follow-up, 77.6% of the cysts, all cystic echinococcosis (CE) 1 and CE3a cysts according to the World Health Organization Informal Working Group classification, showed various degrees of obliteration. In 11.5% of cysts, all of which were > 10 cm-type CE1, a significant amount of fluid persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 12 publications
3
46
0
Order By: Relevance
“…Moreover, over 7% of PAIR procedures were performed on multivesiculated CE2 and CE3b cysts, which have a high rate of relapses after classic PAIR. 9 Of all cysts treated with ABZ, over 21% were multivesiculated CE2 and CE3b cysts, which are highly prone to relapse after ABZ, 10,11 and 13.5% were inactive CE4 and CE5 cysts (Table 3). In fact, PAIR and ABZ alone were the treatment modalities mostly used for CE3b cysts (33.3% and 44.4%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, over 7% of PAIR procedures were performed on multivesiculated CE2 and CE3b cysts, which have a high rate of relapses after classic PAIR. 9 Of all cysts treated with ABZ, over 21% were multivesiculated CE2 and CE3b cysts, which are highly prone to relapse after ABZ, 10,11 and 13.5% were inactive CE4 and CE5 cysts (Table 3). In fact, PAIR and ABZ alone were the treatment modalities mostly used for CE3b cysts (33.3% and 44.4%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 19 cysts surgically removed, 13 were classified as CE3b, a stage known to be poorly responsive to other types of treatment. 8,9 Demographic and clinical information for the 14 study patients is summarized in Table 1. Information regarding treatment duration and medical personnel used per case is summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Golemanov et al reported that 8.9% of patients who presented with hydatid cysts of ≥10 cm in diameter developed fistulization when treated a second time by the PAIR method (8).…”
Section: Discussionmentioning
confidence: 99%